GE_GERICHTE P/22375/2020 vom 15. Oktober 2024 - GE Cour de justice (2024)
TENTATIVE(DROIT PÉNAL);ESCROQUERIE;FIXATION DE LA PEINE;SURSIS À L'EXÉCUTION DE LA PEINE;DISPOSITIONS PÉNALES DE LA LCR | LCR.95.al1.leta; CP.22.al1; CP.146.al1; CPP.144.al1